TEACHERS' EFFORTS TO IMPROVE LEARNING ACTIVITIES DURING THE COVID-19 PANDEMIC AT 15 PALU STATE ELEMENTARY SCHOOL - Ni Kadek Rediani; Putu Satya Narayanti; I Ketut Kertayasa (STAH Dharma Sentana Sulawesi Tengah, 2023)
The COVID-19 pandemic has had an impact on several aspects, one of which is education. In education, learning is carried out online and offline, the impact of which affects the efforts of teachers in facilitating student learning. So this study aims to describe the teacher's efforts in increasing learning activities during the COVID-19 pandemic at the 15 Palu State Elementary School. Determination of informants that the researcher uses is purposive sampling, the research uses a qualitative approach, the type of research used is case studies, the methods that researchers use are interview techniques, observation sheets and documentation. Based on the results of the research and discussion that the researchers did, it was obtained from the results of interviews and observation sheets, where the teacher tried to always improve learning activities by providing motivation and reinforcement to students every time the learning schedule started, and the teacher always tried to provide interesting and easy-to-understand learning for students by the assistance of learning media that can support student success, so that learning objectives can be achieved effectively and efficiently during the COVID-19 pandemic.